Effects of Glutamine and Alanine Supplementation on Adiposity, Plasma Lipid Profile, and Adipokines of Rats Submitted to Resistance Training. (2nd November 2019) - Coqueiro, Audrey Yule; Raizel, Raquel; Bonvini, Andrea; Godois, Allan da Mata; Hypólito, Thaís Menezes; Pereira, Jessica Ramos Rocha; Rogero, Marcelo Macedo; Tirapegui, Julio
ABSTRACT: Glutamine and alanine are lipogenic and could prevent the effects of resistance training (RT) in reducing adiposity and modulating lipid profile. Thus, we aimed to investigate the effects of RT and glutamine and alanine supplementation, in their free or conjugated form, on relative epididymal adipose tissue (EAT) and brown adipose tissue (BAT) weight, plasma lipid profile, and adipokines in EAT. Thirty Wistar rats, aged two months, were distributed into five groups: control (CTRL), trained (TRN), trained and supplemented with alanine (ALA), glutamine and alanine in their free form (GLN+ALA), or L-alanyl-L-glutamine (DIP). Trained groups underwent a ladder-climbing exercise for eight weeks, with progressive load increase. Supplementations were offered in a solution with a concentration of 4% in the last 21 days of training. Food consumption and body weight gain were decreased in the TRN group compared with CTRL. RT also reduced relative EAT and BAT weight, while supplementations, especially with ALA, increased adipose tissue mass. RT reduced total cholesterol (TC), triglycerides (TG), and low-density lipoprotein cholesterol (LDL-c) (TRN vs. CTRL), whereas glutamine and alanine supplementation increased TC and LDL-c, impairing lipid profile modulation by physical exercise. RT did not affect the concentrations of adipokines in EAT, but DIP supplementation increased interleukin- (IL-) 6 and IL-10. In conclusion, RT reduced adiposity and modulated lipid profile, whereas glutamine and alanine supplementation increased adiposity and impaired lipid profile but increased the concentration of the anti-inflammatory cytokines IL-6 and IL-10 in EAT.